Experiences of Siblings of Children With Neurodevelopmental Disorders: Comparing Qualitative Analysis and Machine Learning to Study Narratives - Bastiaansen, Jort. A. J.; Veldhuizen, Elien E.; De Schepper, Kees; Scheepers, Floortje E. (Frontiers in Psychiatry, 2022)
Introduction: relatively few studies have focused on the wellbeing, experiences and needs of the siblings of children with a psychiatric diagnosis. However, the studies that have been conducted suggest that the impact of such circumstances on these siblings is significant. Studying narratives of diagnosed children or relatives has proven to be a successful approach to gain insights that could help improve care. Only a few attempts have been made to study narratives in psychiatry utilizing a machine learning approach. Method: in this current study, 13 narratives of the experiences of siblings were collected through largely unstructured interviews. The interviews were analyzed using the traditional qualitative methodology as well as latent Dirichlet allocation (LDA), an unsupervised machine learning method clustering words from documents into topics. One aim of this study was to evaluate the experiences of the siblings. Furthermore, the outcomes of both analyses were compared to evaluate the role of machine learning in analyzing narratives. Results: qualitative analysis of the interviews led to the formulation of nine main themes and several subthemes. Using unsupervised machine learning (LDA) 24 topics were formed that mostly overlapped with the qualitative themes found. Both the qualitative analysis and the LDA analysis detected themes that were unique to the respective analysis. Conclusion: the present study found that studying narratives of siblings of children with a psychiatric disorder contributes to a better understanding of the subjects’ experiences. Siblings cope with ambivalent feelings towards their brother or sister and this emotional conflict often leads to adapted behavior. Several coping strategies are developed to deal with the behavior of their brother or sister. Devoted support, time and attention from close relatives, especially parents, is needed. Finally, it was proposed that LDA could be a valuable addition to the traditional qualitative methods in analyzing narratives.